ETOS EKONOMI KAUM TAREKAT SHIDDIQIYYAH - Syahrul A’dham (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
Congregations are often used as a scapegoat in the deterioration of Islam. Concepts of zuhud, indigent, and trust activities of the congregation are considered distancing from worldly life. So, the lives of the congregation is a fatalist and a life away from the world. This opinion is not entirely true, because apparently Shiddiqiyyah congregation very concerned in economic life. Not only for the sake of his followers, but also for the surrounding community. Moreover, the economic activity they do is considered as a manifestation practice of congregation itself.DOI: